SUPERVISI AKADEMIK DALAM MENINGKATKAN HIGHER ORDER THINKING SKILL (HOTS) DI MADRASAH - Hosnan , Hosnan (Universitas Nurul Jadid, 2020)
This paper describes the strategies used in academic supervision in improving Higher Order Thinking Skills (HOTS) learning. This study uses the literature method because the data obtained comes from online and offline print media with content analysis techniques. In the application of HOTS learning, not all teachers are able to carry it out perfectly, for that, coaching and training are needed first. Questioning about the development of educators, of course, cannot be separated from the role of supervisors who have the role and function of fostering teachers and controlling the learning process of students. The things that are done in academic supervision in improving HOTS learning include (1) Creating harmonious relationships, (2) Needs analysis, (3) Developing strategies and media, (4) Teacher performance appraisal, (5) Follow-up, in terms of This will make changes and improvements based on what has been found in the previous assessment.